Direct oral anticoagulants from the perspective of Czech pharmacists - opinions, attitudes, confidence, and patient education during dispensing in a pharmacy - Dvořáčková, Simona; Malá-Ládová, Kateřina; Mertová, Tereza; Kolmanová, Eliška; Malý, Josef (Ceska a Slovenska farmacie, 2024)
UNLABELLED: Direct oral anticoagulants from the perspective of Czech pharmacists - opinions, attitudes, confidence, and patient education during dispensing in a pharmacy Introduction and Aim: Pharmacists play an important role in the management of anticoagulation therapy, therefore good knowledge and confidence in care of patients treated with anticoagulation are essential. The aim of this study was to analyse the opinions and attitudes of pharmacists in the Czech Republic towards direct oral anticoagulants (DOACs), their perception of the benefits and risks of DOACs, and the position of pharmacists in educating patients about the basic principles of DOAC treatment in the context of dispensing these medicines in pharmacies. METHODS: An online anonymous questionnaire survey conducted in 2021 among pharmacists of three specific District Pharmacists Associations of the Czech Chamber of Pharmacy. The questionnaire included 32 open- and closed-ended questions, and questions for reporting of the level of agreement using a Likert scale. Descriptive statistics, parametric and non-parametric tests were used to evaluate the data. RESULTS: A total of 162 pharmacists participated (14% return rate), 139 of whom dispensed medicines in a pharmacy in the last year. Respondents working in pharmacies located in any health centre and in hospital pharmacies reported dispensing DOACs more frequently (p < 0.001). The majority of respondents (73%) felt completely or rather confident in providing expert information regarding DOACs. Higher confidence was associated with respondents working in hospital pharmacies or pharmacies located in health centres (p < 0.05), working in clinical pharmacy wards (p < 0.05) and being more likely to dispense DOACs in the pharmacy (p < 0.001). Higher confidence was related to the areas pharmacists discussed with patients during DOAC dispensing, e.g., reasons for using DOACs or how to administer. CONCLUSION: The frequency of dispensing DOACs, type of pharmacy, and working as clinical pharmacist influenced respondents' confidence towards DOACs. Confidence may have influenced the course of DOAC dispensing in the pharmacy. Consolidating the pharmacist's position in patient education during DOAC treatment and strengthening pharmacists' confidence in dispensing DOACs should be therefore considered.
Keywords: vzdělávání pacientů jako téma; Attitude of Health Personnel; Česká republika; Middle Aged; průzkumy a dotazníky; mužské pohlaví; aplikace orální; Adult; postoj zdravotnického personálu; Czech Republic; Health Knowledge, Attitudes, Practice; pharmacists, DOACs, attitude, opinions, education; antikoagulancia; ženské pohlaví; Humans; Anticoagulants; farmaceuti; Surveys and Questionnaires; Patient Education as Topic; lidé středního věku; Administration, Oral; dospělí; zdraví - znalosti, postoje, praxe; Female; Pharmacists; lidé; Male